Adsorption of H2 and C2H2 onto Rh-decorated InN monolayer and the effect of applied electric field. (3rd April 2022) - Wang, Haiming; Wu, Hailong; Cui, Hao
Abstract : InN monolayer with graphene-like morphology and desirable electronic property is a promising candidate for gas sensing application. In this paper, we study the adsorption and sensing performances of the Rh-decorated InN (Rh–InN) monolayer upon two typical dissolved gases in the transformers oil, namely H2 and C2 H2, to explore its potential to evaluate the working condition of the transformers. Rh atom conducts n-doping on the pristine InN surface with E b of −2.01 eV. Also, chemisorption is determined for H2 and C2 H2 adsorption on the Rh–InN surface given that the E ad of −0.88 and −2.15 eV, respectively. The opposite changing trend of E g in H2 and C2 H2 systems manifests the resistance-based sensing mechanism for selective detection of two gas species. The applied electric field supports the work function analysis that an Rh–InN monolayer possesses a strong potential for field-effect transistor sensor application in terms of H2 and C2 H2 detection, wherein the charge-transfer in the gas systems is tunable by altering the voltage. Moreover, the excessive electric field is not considered to be suggestible since it can impact the geometric stability of the Rh–InN monolayer. This theoretical work is meaningful to exploit novel sensing 2D materials to guarantee the good operation of the power system. Highlights Rh-decorating behaviors upon InN monolayer is studied. Expound the potential of Rh-InN monolayer for dissolved gas analysis in transformers. Analyze the effect of applied electric field on gas adsorptions. GRAPHICAL ABSTRACT: UF0001